Therapist guided internet based cognitive behavioural therapy for body dysmorphic disorder: single blind randomised controlled trial. (2nd February 2016) - Enander, Jesper; Andersson, Erik; Mataix-Cols, David; Lichtenstein, Linn; Alström, Katarina; Andersson, Gerhard; Ljótsson, Brjánn; Rück, Christian
Abstract : Objectives To evaluate the efficacy of therapist guided internet based cognitive behavioural therapy (CBT) programme for body dysmorphic disorder (BDD-NET) compared with online supportive therapy. Design A 12 week single blind parallel group randomised controlled trial. Setting Academic medical centre. Participants 94 self referred adult outpatients with a diagnosis of body dysmorphic disorder and a modified Yale-Brown obsessive compulsive scale (BDD-YBOCS) score of ≥20. Concurrent psychotropic drug treatment was permitted if the dose had been stable for at least two months before enrolment and remained unchanged during the trial. Interventions Participants received either BDD-NET (n=47) or supportive therapy (n=47) delivered via the internet for 12 weeks. Main outcome measures The primary outcome was the BDD-YBOCS score after treatment and follow-up (three and six months from baseline) as evaluated by a masked assessor. Responder status was defined as a ≥30% reduction in symptoms on the scale. Secondary outcomes were measures of depression (MADRS-S), global functioning (GAF), clinical global improvement (CGI-I), and quality of life (EQ5D). The six month follow-up time and all outcomes other than BDD-YBOCS and MADRS-S at 3 months were not pre-specified in the registration at clinicaltrials.gov because of an administrative error but were included in the original trial protocol approved by the regional ethics committee before the start of the trial. Results BDD-NET was superior to supportive therapy and was associated with significant improvements in severity of symptoms of body dysmorphic disorder (BDD-YBOCS group difference −7.1 points, 95% confidence interval −9.8 to −4.4), depression (MADRS-S group difference −4.5 points, −7.5 to −1.4), and other secondary measures. At follow-up, 56% of those receiving BDD-NET were classed as responders, compared with 13% receiving supportive therapy. The number needed to treat was 2.34 (1.71 to 4.35). Self reported satisfaction was high. Conclusions CBT can be delivered safely via the internet to patients with body dysmorphic disorder. BDD-NET has the potential to increase access to evidence based psychiatric care for this mental disorder, in line with NICE priority recommendations. It could be particularly useful in a stepped care approach, in which general practitioner or other mental health professionals can offer treatment to people with mild to moderate symptoms at low risk of suicide. Trial registration ClinicalTrials.gov ID: NCT02010619 .